Morning blood pressure surge is associated with the severity of stable coronary artery disease in hypertensive patients - Hazar Harbalıoğlu; Onur Kaypaklı (Clinical and Experimental Hypertension, 2021)
Background: We aimed to investigate the association between morning surge (MS) of blood pressure (BP) and SYNTAX score (SS) which gives information regarding the complexity and extent of coronary artery disease (CAD) in hypertensive patients.  Methods: We included 187 hypertensive patients (134 males, 53 females; mean age: 62.5 ± 10.9 years) who underwent elective coronary angiography. Patients with the acute coronary syndrome and a history of coronary intervention were excluded from the study. The MBPS was calculated as the difference between the average BP during the 2 hours after awakening (four BP readings) and the lowest nighttime BP. The severity of coronary lesions was evaluated based on the SS assessed by coronary angiography. Patients were classified into two groups according to SS: low SS (SS ≤ 22) and intermediate-to-high SS (>22). Results: Patients in the intermediate-to-high SS group were found to be older, have higher uric acid levels, average daytime systolic BP (SBP), nighttime SBP, morning SBP, MS of BP and have higher rates of diabetes (DM) and female gender. There was no significant difference in terms of hypertensive treatment. In multivariate analysis, MS of BP (OR: 2.151, p: 0.005) and DM (OR: 0.014, p: 0.015) were independent parameters for predicting intermediate-to-high SS. The cutoff value of MS of BP obtained by ROC curve analysis was 18,5 mmHg for prediction of intermediate–high SS (sensitivity: 76.5%, specificity: 71.2%). The area under the curve was 0.762 (p < .001). Conclusion: MS of BP significantly correlates with the severity of coronary stenosis in hypertensive patients, suggesting that it could be a potential predictive marker of CAD.